Diseño de un sistema de protección para el generador eléctrico de la Universidad Técnica de Cotopaxi La Maná - Allauca Gonzalez, Franklin Humberto (2014)
Generators represent overvalued equipment in a power electrical system and are subjected, more than other systems, to abnormal functioning conditions, that is why there has to be a special care in the protection system necessary for the generator. The actual Project is a protection system for a diesel emergency generator. The electrical protection makes up an indispensable system for any kind of electrical installation, in the case of a protection system for a generator, the protection has to do with high standards of abnormal functioning in comparison with the protection of the element of the system